Level of Establishment of the Committee of Early Detection of Risk in Turkey: Example of İstanbul Chamber of Industry Top 500 Industrial Enterprises (Third Sector Social Economic Review, 2025)
Developments in the world since the industrial revolution have brought new management practices to the agenda; company bankruptcies and scandals, especially in the 2000s, have brought "corporate governance" practices to the agenda and increased the importance of detecting any negativities that may threaten the existence of companies in advance and taking necessary measures. Establishing a committee at the board level has become one of the solutions, and with the legal regulations, committee of early detection of risk (CEDR) has gained a legal status. However, the legislative provisions do not make the committee in question mandatory for all types of companies, and sufficient regulations have not been made regarding the formation, duties and powers of the committee. The aim of the study is to determine the level of establishment of RESK without a legal obligation. In this context, companies that are required to establish RESK as well as companies that do not have a legal obligation to establish RESK, were selected as examples from the list of "Top 500 Industrial Enterprises" announced by the Istanbul Chamber of Industry (ISO) for 2022, which includes companies that are required to establish RESK. As a result of this study, it was found that 80% of the 99 companies whose data could be accessed had CEDR, and that the provisions of the legislation were complied with to a significant extent regarding committee formation and activities.
Keywords: Committee of Early Detection of Risk; Risk Management; Corporate Govarnance; Content Analysis; Top 500 Industrial Enterprises